Survival Analysis of Cancer Patients With FIGO Stage IIIA Endometrial Cancer. (June 2015) - Lum, Marija M.; Belnap, Thomas W.; Frandsen, Jonathan; Brown, Aaron P.; Sause, William T.; Soisson, Andrew P.; Dodson, Mark K.; Werner, Theresa; Gaffney, David K.
<x xml:space="preserve">Abstract</x> Objective: Endometrial cancer patients with positive serosa and/or adnexae (FIGO stage IIIA) have a variable prognosis and are at a significant risk for recurrence. We investigated how tumor characteristics and adjuvant treatments influence the overall survival (OS) and recurrence patterns in these patients and patients with positive cytology alone (previously classified as stage IIIA before 2009). Materials and Methods: This multi-institution retrospective study reviewed 55 patients with positive serosa and/or adnexae and 18 patients with positive cytology only, surgically staged from 1990 to 2010. The study cohort was evaluated using the Kaplan-Meier estimates of OS and Cox proportional hazards modeling. Results: The 5-year OS for all IIIA patients was 55%. Administration of adjuvant therapy was associated with improved OS when compared with surgery alone (P=0.0018). The 5-year OS was 20% for patients treated with surgery alone (n=10), 55% with surgery and radiation therapy (n=26), 75% with surgery and chemotherapy (n=7), and 79% with surgery followed by both radiation therapy and chemotherapy (n=12; P=0.005). The tumor characteristics showed that nonendometrioid histology (P=0.0143) and lymph vascular space invasion (P=0.0483) had a poorer OS. Recurrence occurred in 29% of IIIA patients, with 9% locoregional failures and 20% distant failures. Patients with positive cytology only had a similar OS to patients with positive serosa and/or adnexae (76% vs. 55%; P=0.104) and recurrence rate (22% vs. 29%; P=0.4101). Conclusions: This retrospective study suggests benefit from the use of adjuvant radiotherapy and chemotherapy for stage IIIA patients. We recommend further investigation of adjuvant therapies for IIIA patients in prospective studies and randomized clinical trials.